Effects of annealing on the crystallization and roughness of PLZT thin films - Simoes, A. Z.; Gonzalez, AHM; Zaghete, M. A.; Varela, José Arana [UNESP]; Stojanovic, B. D. (Elsevier B.V., 2001)
Lead lanthanum zirconate titanate (PLZT) thin films with stoichiometry (9/65/35) were prepared by a dip-coating process using a polymeric organic solution. The solution viscosity was adjusted in the range of 15-56 cP. Silicon (100) substrates were previously cleaned and then immersed in the solution. The withdrawal speed of substrate from the solution was adjusted within a range of 5 to 20 mm/min. The coated substrates were thermally treated in the 450-700 degreesC temperature range. Surface roughness and crystallization of these films are strongly dependent on the annealing conditions. Infrared and X-ray diffraction data for PLZT powders heat-treated at 650 degreesC for 3 h show that the material is free of carbonate phases and crystalline. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: annealing; crystallization; surface roughness; x-ray diffraction